Visual Evoked Potential and Magnetic Resonance Imaging are More Effective Markers of Multiple Sclerosis Progression than Laser Polarimetry with Variable Corneal Compensation - Kantorová, Ema; Žiak, Peter; Koyšová, Mária; Kurča, Egon; Michalik, Jozef; Hladká, Mária; Zeleňák, Kamil (Frontiers in Human Neuroscience, 2014)
Backround: The aim of our study was to assess the role of laser polarimetry and visual evoked potentials as potential biomarkers of disease progression in multiple sclerosis (MS). Participants: A total of 41 patients with MS (82 eyes) and 22 age-related healthy volunteers (44 eyes) completed the study. MS patients were divided into two groups, one (ON) with a history of optic neuritis (17 patients, 34 eyes) and another group (NON) without it (24 patients, 48 eyes). The MS patients and controls underwent laser polarimetry (GDx) examination of the retinal nerve fibre layer (RNFL). In the MS group we also examined: Kurtzke "Expanded disability status scale" (EDSS), the duration of the disorder, visual evoked potentials (VEP) – latency and amplitude – and conventional brain MRI. Results: In the MS group, brain atrophy and new T2 brain lesions in MRI correlated with both VEP latencies and amplitudes. Separate comparisons revealed VEP latency testing to be less sensitive in ON than in NON patients. In ON patients, VEP amplitudes correlated mildly with brain atrophy (r =-0.15) and strongly with brain new MRI lesions (r = -0.8). In NON patients, highly significant correlation of new MRI brain lesions with VEP latencies (r = 0.63, r = 0.6), and amplitudes ( r = -0.3, r = -4.2) was found. EDSS also correlated with brain atrophy in this group (r = 0.5). Our study did not find a correlation of GDx measures with MRI tests. The GDx method was not able to detect whole brain demyelinisation and the degeneration process, but was only able to reveal the involvement of optic nerves in ON and NON patients. Conclusions: In our study, we found that both methods (VEP and GDx) can be used for detection of optic nerve damage, but VEP was found to be superior in evaluating whole brain demyelinisation and axonal degeneration. Both VEP and MRI, but not GDx, have an important role in monitoring disease progression in MS patients, independent of the ON history.